Pain in hereditary neuropathy with liability to pressure palsy: An association with fibromyalgia syndrome?. Issue 3 (March 2015) - Yilmaz, Ugur; Bird, Thomas T.; Carter, Gregory T.; Wang, Leo H.; Weiss, Michael D.
ABSTRACT Introduction: This study characterizes the nature of pain in hereditary neuropathy with liability to pressure palsy (HNPP). Methods: This retrospective study was performed to assess duration, nature, location, and intensity of pain on initial presentation of subjects with HNPP, including the degree and type of analgesic medication use and electrodiagnostic characteristics. Subjects who met the American College of Rheumatology criteria for fibromyalgia syndrome (FMS) were also identified. Results: Of 32 HNPP subjects, 24 (75%) had symptoms of pain, and 4 (12%) had pain as an initial symptom. Of subjects who described pain, 9 (28%) reported only musculoskeletal pain, 10 (31%) only neuropathic pain, and 5 (16%) both musculoskeletal and neuropathic pain. All 9 subjects with only musculoskeletal pain met criteria for FMS. Conclusions: Neuropathic and musculoskeletal pain occur commonly in HNPP and may be a presenting symptom. Additionally, HNPP with predominantly musculoskeletal pain may meet criteria for FMS and potentially delay the diagnosis. Muscle Nerve51: 385–390, 2015